2015
DOI: 10.3233/cbm-150534
|View full text |Cite
|
Sign up to set email alerts
|

Application of platelet/lymphocyte and neutrophil/lymphocyte ratios in early diagnosis and prognostic prediction in patients with resectable gastric cancer

Abstract: PLR and NLR measurements can provide important diagnostic and prognostic results in patients with resectable gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
99
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(107 citation statements)
references
References 0 publications
7
99
0
1
Order By: Relevance
“…This finding is consistent with other smaller studies demonstrating that elevated NLR portends poor prognosis in solid tumor malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Other studies in patients with hepato-pancreato-biliary (HPB) cancers agree with the findings presented in this paper. In a study of 452 patients who underwent a HPB procedure for malignant disease, NLR >5 was found to be associated with worse OS.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with other smaller studies demonstrating that elevated NLR portends poor prognosis in solid tumor malignancies. [1][2][3][4][5][6][7][8][9][10][11][12][13] Other studies in patients with hepato-pancreato-biliary (HPB) cancers agree with the findings presented in this paper. In a study of 452 patients who underwent a HPB procedure for malignant disease, NLR >5 was found to be associated with worse OS.…”
Section: Discussionsupporting
confidence: 91%
“…Elevated NLR is independently associated with worse outcomes in cancers of the breast, 1,2 thyroid, 3 colon, 4 stomach, 5 prostate, 6 lung, 7 adrenal, 8 pancreas 9,10 urogenital tract, 11 esophagus 12 and in glioblastoma, 13 as well as hematologic cancers, including multiple myeloma 14 and diffuse large B-cell lymphoma. 15 According to a recent systematic review and meta-analysis including 100 studies and greater than 40,000 patients, high NLR is associated with adverse overall survival (OS) in many solid tumors.…”
Section: Introductionmentioning
confidence: 99%
“…An elevated NLR is considered to be associated with elevated circulating concentrations of these cytokines, which offers an insight into mechanisms underlying an elevated NLR (30,31). Nevertheless, the cutoff points of NLR proposed in previous studies differ, including NLR thresholds of 2.3, 4.02 or 5 in gastric cancer (14,32,33), 0.38, 2.4 or 3 in colorectal cancer (15,34,35), 2.3 or 2.5 in NSCLC (10,36), and consensus has not been established. The heterogeneity of those studies may contribute to the different results.…”
Section: Discussionmentioning
confidence: 96%
“…A number of inflammation markers have been evaluated to stratify patients for treatment and to predict survival (9). The prognostic value of preoperative systemic inflammationrelated neutrophil-lymphocyte ratio (NLR) and plateletlymphocyte ratio (PLR) has been demonstrated in patients with a variety of cancers (10)(11)(12)(13)(14)(15)(16)(17)(18). However, no previous studies have evaluated the association between NLR and PLR with the prognosis of thymic tumors.…”
Section: Original Articlementioning
confidence: 99%
“…As early as 1863, Rudolf Virchow, who suggested that lymphoreticular infiltration reflected the origin of cancer at sites of chronic inflammation, identified a connection between inflammation and cancer (16). Subsequently, numerous studies have provided evidence that the host inflammatory responses serve a critical function in various aspects of cancer, including cancer initiation, promotion, progression and metastasis (7,(17)(18)(19) Previously, a number of inflammatory markers have been proposed to have potential for use as predictors of OS and PFS for solid tumors (8,12,(20)(21)(22)(23). The present study identified that NLR, LMR and PLR may be able to predict the prognosis of patients with DLBCL.…”
Section: Discussionmentioning
confidence: 99%